Food insecurity and health: data from the veterans aging cohort study. - Wang, Emily A; McGinnis, Kathleen A; Goulet, Joseph; Bryant, Kendall; Gibert, Cynthia; Leaf, David A; Mattocks, Kristin; Fiellin, Lynn E; Vogenthaler, Nicholas; Justice, Amy C; Fiellin, David A (Public health reports (Washington, D.C. : 1974), 2015)
Food insecurity may be a modifiable and independent risk factor for worse control of medical conditions, but it has not been explored among veterans. We determined the prevalence of, and factors independently associated with, food insecurity among veterans in the Veterans Aging Cohort Study (VACS).